Nexus between real effective exchange rate misalignment and rubber export in Nigeria - Mukaila, Ridwan (Economic Journal of Emerging Markets, 2021)
Purpose - This study examines the nexus between the real effective exchange rate misalignment (REERM) and rubber exports in Nigeria. The effects of equilibrium real exchange rate (ERER) and some economic fundamentals on rubber exports are also investigated. Methods - Johansen cointegration, vector error correction model and Granger causality test are employed as methods of data analysis. Findings - The results show that a long-run relationship exists between REERM and rubber export. REERM influenced rubber export negatively while ERER had a positive effect on rubber export. The past values of REERM can be used to predict the present volume of rubber export, and the past values of ERER and rubber export can be used to forecast the present values of each other. Trade openness positively influences rubber export while the term of trade has a negative effect on rubber export. Implication - REERM worsens the performance of rubber export in Nigeria while ERER improves its performance. Thus, rubber export can be enhanced through measures such as trade openness, improved term of trade and monitoring of exchange rate to reduce the REERM and maintain a stabilized equilibrium exchange rate system. Originality - This study focuses on the effect of deviation of the exchange rate from equilibrium, ERER and economic fundamentals on rubber export which has not been previously investigated.